The Asian financial crisis and global finalcial crisis: evidence from Asean Free Trade Area - Ismail, Normaz Wana (2012)
This study empirically investigates the effect of the two series of financial crisis on intra ASEAN trade. Using the gravity model, this study further examines whether the formation of the ASEAN Free Trade Area (AFTA) resulted in an increase in intra ASEAN trade for the period 1986 to 2010. From basic gravity variables, the study found that market size, population, relative endowment, distance and common border are the main determinants of bilateral trade in ASEAN. The results reveal that the Asian financial crisis in 1997-98 did trigger the intra ASEAN trade compared to the global crisis in 2007-08. Closer examination also shows that the establishment of AFTA increases trade creation in the region as most of members already removed tariff among members.